PENGARUH TEMAN SEBAYA TERHADAP PERILAKU KONSUMTIF MAHASISWA BIMBINGAN DAN KONSELING DI UNIVERSITAS ISLAM NEGERI SJECH M.DJAMIL DJAMBEK BUKITTINGGI - Ruji; Afrinaldi; Junaidi; Fadhilla Yusri (STKIP Subang, 2026)
The phenomenon that occurs in students who tend to make purchases of goods not because of need, but because of the influence of the friendship environment and the desire to follow trends. Peers have an important role in the process of socialization and the formation of student lifestyles, including in daily consumption patterns. This study aims to determine the influence of peers on the consumer behavior of guidance and counseling students at the State Islamic University (UIN) Sjech M. Djamil Djambek Bukittinggi. The research method used is quantitative correlation with a Likert scale questionnaire as a data collection tool. The study population was 146 students, with a sample of 107 people selected using the proportionate stratified random sampling technique. The results of the data analysis showed a significant influence of peers on student consumer behavior, with a significant value of 0.004. The coefficient of determination value of 7.6% indicates that peers contribute to influencing student consumer behavior, although in the low category. These results are in accordance with the theory that states that individuals tend to adjust consumption behavior to be accepted in their social groups. This study is expected to be an input for students to be wiser in managing finances and choosing a healthy social environment.